2019
DOI: 10.3399/bjgp19x707369
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ descriptions of the relation between physical symptoms and negative emotions: a qualitative analysis of primary care consultations

Abstract: BackgroundPrimary care guidelines for the management of persistent, often ‘medically unexplained’, physical symptoms encourage GPs to discuss with patients how these symptoms relate to negative emotions. However, many GPs experience difficulties in reaching a shared understanding with patients.AimTo explore how patients with persistent symptoms describe their negative emotions in relation to their physical symptoms in primary care consultations, in order to help GPs recognise the patient’s starting points in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Assessing emotion understanding and regulation could be a valuable first screen of psychiatric symptoms. Studies in primary care settings have also indicated an association between negative emotions (e.g., low mood, guilt, frustration) and physical health (Bekhuis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing emotion understanding and regulation could be a valuable first screen of psychiatric symptoms. Studies in primary care settings have also indicated an association between negative emotions (e.g., low mood, guilt, frustration) and physical health (Bekhuis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, when the GP introduced this link it tended to be denied. 30 This again underlines the stigma that still pertains on mental distress and its relation to physical health.…”
Section: Discussionmentioning
confidence: 94%
“…These latter explanations typically put forward the psycho-analytic notion that mental distress has evolved into body symptoms. In addition to being scientifically untestable, this approach has resulted in fractious clinical consultations and often hostile rejection by patients and support groups ( Bekhuis et al, 2020 ; Rief and Broadbent, 2007 ).…”
Section: Biological and Psychological Paradigmsmentioning
confidence: 99%